Joseph : a man of integrity and forgiveness : profiles in character - Swindoll, Charles R. (Nashville, Tenn. : Word Pub., 1998)
Charles Swindoll shows us the heart and soul of a man shaped in the crucible of rejection, loneliness, deprivation, and false accusation, a man who learned patience and obedience by becoming totally dependent on God-so dependent that God could use him as a conduit of blessing. Through Joseph God explained dreams, revealed the future, and saved Egypt and Israel from starvation. And, as Chuck Swindoll shows in this book, God's blessings still flow through Joseph, giving us a heartening example of courage, integrity, and forgiveness in the face of cruelty, temptation and hatred. Jospeh's pardon of his cruel brothers demonstrates the depth of love God has for all of us.
1. Favored son, hated brother -- 2. Resisting temptation -- 3. Imprisoned and forgotten -- 4. Remembered and promoted -- 5. Reaping the rewards of righteousness -- 6. Activating a seared conscience -- 7. Groanings of a sad dad -- 8. Fear displaced by grace -- 9. "I am Joseph!" -- 10. The ultimate family reunion -- 11. On-the-job integrity -- 12. Highlights of twilight and midnight.
Includes bibliographical references (p. 213-218).
Keywords: Joseph -- (Son of Jacob); Patriarchs (Bible) -- Biography; Joseph -- (Son of Jacob); Joseph -- (Son of Jacob); Patriarchs (Bible); Biography